2021
DOI: 10.1002/ehf2.13643
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic and anticoagulation therapies in cardiogenic shock: a critical review of the published literature

Abstract: Cardiogenic shock (CS) is a complex multifactorial clinical syndrome, developing as a continuum, and progressing from the initial insult (underlying cause) to the subsequent occurrence of organ failure and death. There is a large phenotypic variability in CS, as a result of the diverse aetiologies, pathogenetic mechanisms, haemodynamics, and stages of severity. Although early revascularization remains the most important intervention for CS in settings of acute myocardial infarction, the administration of timel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 169 publications
(427 reference statements)
0
11
0
Order By: Relevance
“…77 Therapeutic anticoagulation with unfractioned heparin or low molecular weight heparin (LWMH) is mandatory when PE is diagnosed. 78,79 These patients require very cautious fluid loading to avoid RV overdistension and IV vasopressors in case of haemodynamic instability. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) may be considered when RV dysfunction progress to CS.…”
Section: Different Hf Phenotypes Associated With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…77 Therapeutic anticoagulation with unfractioned heparin or low molecular weight heparin (LWMH) is mandatory when PE is diagnosed. 78,79 These patients require very cautious fluid loading to avoid RV overdistension and IV vasopressors in case of haemodynamic instability. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) may be considered when RV dysfunction progress to CS.…”
Section: Different Hf Phenotypes Associated With Covid-19mentioning
confidence: 99%
“…Similarly, recurrent pulmonary microembolization or massive embolism will suddenly increase RV pressure with progressive alterations of RV systolic performance and compliance 77 . Therapeutic anticoagulation with unfractioned heparin or low molecular weight heparin (LWMH) is mandatory when PE is diagnosed 78,79 . These patients require very cautious fluid loading to avoid RV overdistension and IV vasopressors in case of haemodynamic instability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that platelet aggregation may be enhanced in low-flow states and hypothermia, now routine in treatment of resuscitated CA. 12 In addition, gastric motility is decreased in these CS and CA patients, which slows down the absorption of oral therapeutics. 12 When this enhanced platelet reactivity is combined with the low-flow state in all patients in CS and most patients with resuscitated CA, the environment is right for enhanced thrombus formation.…”
mentioning
confidence: 99%
“…12 In addition, gastric motility is decreased in these CS and CA patients, which slows down the absorption of oral therapeutics. 12 When this enhanced platelet reactivity is combined with the low-flow state in all patients in CS and most patients with resuscitated CA, the environment is right for enhanced thrombus formation. However, a study by Ibrahim et al 13 showed increased platelet inhibition and less high on-treatment platelet reactivity with prasugrel or ticagrelor in patients after CA treated with hypothermia, giving biological plausibility to the findings by Patlolla et al The unknown factor in reducing early events in the CS/CA patient population is whether an intravenous drug such as cangrelor early in treatment followed by a transition to an oral agent would provide better results as cangrelor does not rely on gastrointestinal absorption or hepatic metabolism to inhibit platelets.…”
mentioning
confidence: 99%
“…8,9 In patients with acute coronary syndrome (ACS), morphine may be used to reduce pain, dyspnoea or anxiety, but it attenuates platelet inhibition because of slower absorption, delayed onset of action, and reduced bioavailability of oral anti-platelet agents. 10,11 This is particularly relevant in cardiogenic shock where, beyond its vasodilatory effects, morphine causes splanchnic hypoperfusion with further delay of gastric motility and decreased bioavailability of all oral drugs. 11 Consequently, morphine is not routinely recommended in the management of patients with ACS and AHF.…”
mentioning
confidence: 99%